Collagen and Microvascularization in Placentas From Young and Older Mares - Neto da Silva, Ana Catarina; Costa, Ana Luísa; Teixeira, Ana; Alpoim-Moreira, Joana; Fernandes, Carina; Fradinho, Maria João; Rebordão, Maria Rosa; Silva, Elisabete; Ferreira da Silva, José; Bliebernicht, Miguel; Alexandre-Pires, Graça; Ferreira-Dias, Graça (Frontiers in Veterinary Science, 2022)
In older mares, increasing collagen fibers (fibrosis) in the endometrium and oviduct predisposes to sub-fertility and infertility. In this study, (i) gene transcription of collagen (qPCR: COL1A1, COL1A2, COL3A1, COL5A1); (ii) total collagen protein (hydroxyproline); (iii) collagen distribution (Picrosirius red staining; polarized light microscopy); and (iv) microvascular density (Periodic acid-Schiff staining), were evaluated in mares’ placenta, and related to mares age, and placenta and neonate weights. Samples were collected from the gravid horn, non-gravid horn, and body of the placenta from younger (n=7), and older mares (n=9) of different breeds. Transcripts of COL1A1, COL3A1 and COL5A1, total collagen protein, chorionic plate connective tissue thickness, and microvascularization increased in the gravid horn of older mares’ placentas, compared to the youngest (P<0.05). Although in other species placenta fibrosis may indicate placental insufficiency and reduced neonate weight, this was not observed here. It appears that older fertile mares, with more parities, may develop a heavier, more vascularized functional placenta with more collagen, throughout a longer gestation, which enables the delivery of heavier foals. Thus, these features might represent morphological and physiological adaptations of older fertile mares’ placentas to provide the appropriate nutrition to the equine fetus.